Development of Multiple Concentrations of Phosphorus and Ammonium-Nitrogen Calibration Curve Using Laboratory Resistivity Method at Acidic pH Conditions - BOO, WEI SIANG; Wan Mohamed @ Wan Abd Ghani, Wan Afnizan (Recent Trends in Civil Engineering and Built Environment, 2021)
Phosphorus and nitrogen are important element to the living ecosystem, but the amount should be in optimum level. The amount of concentration will bring effect towards the water quality and the surrounding ecosystem. Water resistivity method can be applied in-situ to obtain the resistivity value of the water body. This study was proposed to develop the phosphorus and ammonium-nitrogen concentration calibration curve using laboratory resistivity method in acidic pH condition. A laboratory experiment was conducted to obtain the resistivity value of different concentration of phosphorus and ammonium-nitrogen in different pH value of acidic solution varies from 3.0 to 6.4  with 0.2 interval. The resistivity value was obtained using electrical resistivity box and analysed to develop the calibration curve. The concentration of phosphorus and ammonium-nitrogen standard was divided into three ranges which is (low = 1 - 10 mg P/L + 1 - 100 mg NH4-N/L). (medium = 11 - 100 mg P/L + 101 - 1000 mg NH4-N/L); and (high = 101 - 1000mg P/L + 1001 - 2000 mg NH4-N/L). The calibration curve which reflects the relationship between phosphorus and ammonium-nitrogen concentration and resistivity value will be developed. The expected results in this lab experiment had shown the concentration of the phosphorus and ammonium-nitrogen is inversely proportional to the resistivity value.